The Impact of VR Exhibition Experiences on Presence, Interaction, Immersion, and Satisfaction: Focusing on the Experience Economy Theory (4Es) - Sungbok Chang; Jungho Suh (Systems)
This study systematically analyzes and emphasizes the importance of VR exhibition experiences, a relatively under-researched area. It examines the effects of VR exhibition experiences on presence and interaction and the influence of interaction on presence. Additionally, how these factors impact user immersion and satisfaction is explored, and the relationship between exhibition immersion and satisfaction is analyzed. Specifically, this study investigates how virtual exhibition experiences, similar to those in physical galleries, provide a sense of reality, leading to immersion in the artwork and ultimately resulting in satisfaction. The findings reveal that, among the VR exhibition experience factors, entertainment, escapism, and aesthetic experiences positively (+) affected interaction, while educational experiences negatively (−) influenced it. Furthermore, entertainment, escapism, and educational experiences positively influenced presence, whereas aesthetic experiences did not significantly impact it. Interaction significantly affected presence and positively influenced both immersion and satisfaction. Presence positively affected immersion but did not significantly affect satisfaction. Finally, immersion positively affected satisfaction. This study suggests that strategies that enhance interaction and presence are crucial in designing VR exhibition experiences. They also provide an important foundation for future research by systematically analyzing the relationships between presence, interaction, immersion, and satisfaction in VR exhibition experiences.